RELEVANSI GEOGRAFIS DAN AKTIVITAS EKONOMI WISATA SUMBER GEMPONG SEBAGAI SUMBER BELAJAR IPS KELAS VIII - Anindita Nasywa Pramesti; Putri Yasmin Efendi; Annisa Dewi Meida Ashok Putri; Radiffa Zabrina Cinta; Silvi Nur Afifah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Social Studies (IPS) instruction is currently still dominated by a theoretical approach that fails to integrate the realities of the surrounding environment into classroom materials. This study aims to analyze the interactions between geographical conditions, environmental utilization, and community economic activities in Sumber Gempong, Trawas, Mojokerto, as well as to examine their relevance as a source of contextual IPS learning for eighth-grade students. A descriptive qualitative approach was applied to process the data obtained through field observations and in-depth interviews with managers, merchants, farmers, and tourists using purposive sampling. The data analysis process utilized an interactive model encompassing data reduction, presentation, and drawing conclusions. Findings indicate that the mountainous geographical conditions with abundant water sources support the optimization of the tourism sector, horticultural agriculture, and the empowerment of MSMEs. However, a challenge was identified in the form of a decline in visitor numbers over the past five years due to suboptimal promotional strategies. Regardless of these aspects, the phenomenon at Sumber Gempong represents a tangible interconnection between geographical space and human activities that holds significant potential as a learning resource. It can be concluded that integrating the local environment into the curriculum enhances students’ conceptual understanding and active engagement in social studies learning. ABSTRAK Pembelajaran Ilmu Pengetahuan Sosial (IPS) saat ini masih didominasi oleh pendekatan teoritis yang kurang mengintegrasikan realitas lingkungan sekitar ke dalam materi kelas. Kajian ini diarahkan untuk menganalisis interaksi antara kondisi geografis, pemanfaatan lingkungan, dan aktivitas ekonomi masyarakat di Sumber Gempong, Trawas, Mojokerto, serta mengkaji relevansinya sebagai sumber belajar IPS kontekstual bagi siswa kelas VIII. Pendekatan kualitatif deskriptif diterapkan dalam mengolah data yang diperoleh melalui observasi lapangan dan wawancara mendalam dengan pengelola, pedagang, petani, serta wisatawan melalui teknik purposive sampling. Proses analisis data menggunakan model interaktif yang meliputi reduksi, penyajian, dan penarikan kesimpulan. Temuan menunjukkan bahwa kondisi geografis pegunungan dengan sumber air melimpah mendukung optimalisasi sektor pariwisata, pertanian hortikultura, dan pemberdayaan UMKM. Namun, ditemukan kendala berupa penurunan jumlah kunjungan dalam lima tahun terakhir akibat strategi promosi yang belum optimal. Terlepas dari aspek tersebut, fenomena di Sumber Gempong merepresentasikan keterkaitan nyata antara ruang geografis dan aktivitas manusia yang sangat potensial dijadikan sumber belajar. Dapat disimpulkan bahwa integrasi lingkungan lokal ke dalam kurikulum mampu meningkatkan pemahaman konseptual dan keterlibatan aktif siswa dalam pembelajaran IPS.